Pré-concentração de Cd(II), Cr(III), Cu(II) e Ni(II) em coluna contendo oxicelulose - Padilha, Pedro de Magalhães; Federici, Cilene do Carmo; Campos, Joaquim Theodoro de Souza; Moreira, José Celso (Eclética Química, 1995)
.